Migration, Access to Capital, and Household Characteristics in Urban Poverty - Dhani, Haris Rama; Syafitri, Wildan (Journal of Development Economic and Social Studies, 2026)
Urban poverty remains a persistent structural challenge, particularly amid increasing population mobility and unequal access to economic resources. This study examines the role of migration, access to capital, and household characteristics in shaping household poverty in Malang City. Using data from the 2024 National Socioeconomic Survey (Susenas), this research applies a quantitative approach with binary logistic regression to 830 household observations. The analysis incorporates migration status, access to capital, number of dependents, educational attainment, and employment status as key explanatory variables. The estimation results indicate that migration, access to capital, higher education, and formal employment are associated with a lower probability of household poverty, while a greater number of dependents significantly increases poverty risk. These findings highlight the importance of economic capacity and demographic characteristics in determining urban poverty vulnerability. The study underscores the need for targeted urban poverty reduction policies that emphasize expanded access to capital, workforce quality improvement, and enhanced support for households facing high dependency burdens.